PERAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK, PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN SUMBA TIMUR TERHADAP PERLINDUNGAN HAK PEREMPUAN DAN HAK ANAK - Ndelo, Heryanto H; Monteiro, Josef M; Rema, Agnes D (Petitum Law Journal, 2025)
His study aims to analyze the role and effectiveness of the Office of Women's Empowerment and Child Protection, Population Control, and Family Planning of East Sumba Regency in protecting the rights of women and children. The research is motivated by the persistent challenges faced by women and children, including gender-based violence, discrimination, and limited access to health, education, and legal protection, particularly in East Sumba, a region marked by traditional patriarchal culture and geographic isolation. Using a juridical-empirical method, data were collected through interviews and document studies involving key officials and community members. The results indicate that while the DP3AP2KB has implemented various programs and policies based on national and regional regulations, several inhibiting factors—such as limited budget, inadequate human resources, and lack of public awareness—have hampered the effectiveness of these initiatives. This study emphasizes the need for stronger institutional support, inter-agency collaboration, and community participation to enhance the protection and empowerment of women and children in the region.